Lifetime utilization of mammography among Maltese women: a cross-sectional survey - Danika Marmarà; Vincent Marmarà; Gill Hubbard (BMC, 2018)
Abstract Background The knowledge of Maltese women not attending the Maltese Breast Screening Programme (MBSP) for mammography screening is scarce. Previous research has identified two distinct groups of non-attendees: those who do not attend because a mammogram was taken elsewhere and those who never attended for mammography anywhere. It is however unknown which determinants are predictive of lifetime attendance 'anywhere' and 'real' non-attendance. The present study examines the relationship between ever-using (Lifetime attendees) or never using mammography (Lifetime non-attendees) and psychosocial - as well as sociodemographic factors, with the aim to identify predictors that can inform practice. Methods Women's characteristics, knowledge, health beliefs and illness perceptions were compared, based on prior data of 404 women, aged 50-60 years at the time of their first MBSP invitation. The main variable of interest described women's attendance to mammography (LIFETIME ATTENDEES) and no mammography (LIFETIME NON-ATTENDEES). Data were analyzed using descriptive statistics, chi-square tests, Mann Whitney test, Independent Samples t-test, Shapiro Wilk test and logistic regression. Results During their lifetime, 86.1% of Maltese women (n = 348) were attendees, while 13.9% (n = 56) were non-attendees. Non-attendees were more likely to be women with a lower family income (χ2 = 13.1, p = 0.011), widowers (χ2 = 9.0, p = 0.030), non-drivers (χ2 = 7.7, p = 0.006), without a breast condition (χ2 = 14.2, p <  0.001), who had no relatives or close friends with cancer (χ2 = 8.3, p = 0.016), and who were less encouraged by a physician (χ2 = 4.9, p = 0.027), unsure of the screening frequency (χ2 = 28.5, p <  0.001), more anxious (p = 0.040) and fearful (p = 0.039). Perceived benefits, barriers, cues to action, self-efficacy and emotional representations were the most significant variables to describe the differences between lifetime attendees and non-attendees. Perceived barriers and cues to action were the strongest predictors for lifetime non-attendance (p <  0.05 respectively). Conclusions The health beliefs of women who have never attended for mammography during their lifetime should be targeted, particularly perceived barriers and cues to action. Further research should focus on understanding knowledge gaps, attitudinal barriers and emotional factors among 'real' non-attendees who require a more targeted approach.